Analysis of Vitamin C Content in Grapefruit (Citrus maxima) Using the Iodimetric Titration Method - Aisya Azzahra; Wa Ode Syafriah; Hasty Hamzah (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Citrus maxima, commonly known as pomelo, is a rich source of nutrients, particularly vitamin C, which is essential for human health. This study focuses on determining the vitamin C content in grapefruit using the iodimetric titration method. Objectives: The primary objective of this research is to quantify the vitamin C levels in grapefruit (Citrus maxima) using the iodimetric titration technique. Methods: The study involves both qualitative and quantitative testing of grapefruit filtrates. The qualitative test includes adding 0.1 N iodine solution to the filtrate in a test tube and noting the number of drops required for the color to change to clear, indicating the presence of vitamin C. For the quantitative analysis, a 1% starch indicator, 0.1 N iodine standard solution, and sodium thiosulfate standard solution were prepared. The 0.01 N iodine solution was standardized using sodium thiosulfate, and the vitamin C content in the grapefruit was determined. Results: The vitamin C content in grapefruit (Citrus maxima) was found to be 3.957 mg/g. Conclusion:This study successfully quantified the vitamin C content in grapefruit using the iodimetric titration method, providing valuable information on its nutritional value. Keywords: Pomelo (Citrus maxima), Vitamin C, Iodimetric titration, Nutritional analysis, Titration method.